ENGLISH SYNONYMIC PROBLEMS THAT UZBEK HAS ENCOUNTERED - Khoshimova, Makhfuza (Журнал иностранных языков и лингвистики, 2020)
THIS ARTICLE IS ABOUT ENGLISH SYNONYMIC PROBLEMS THAT UZBEK HAS ENCOUNTERED